The Need for Life Skills among Adolescents - Awasthi, Seema; Kumari, Chandra (INDIAN EDUCATIONAL REVIEW, 2012)
Adolescence is a crucial phase in human life. It is a critical period of rapid physical, mental and social development. They face numerous challenges in their life such as adjusting to changing body growth and achieving a satisfactory sexual identity, self-identity (self-concept and self-esteem) and choosing a vocation, which leads to the establishment of economic independence. Adolescents have diverse need but their needs are not fulfilled by our education system and they experience gap between school and out of school reality. There is lacuna in education that seems to be getting more obvious as in the form of drug abuse, suicides, depression, violence, declined value system, stressful competition, materialism, and crimes. There is need to understand adolescents’ diverse need and efforts should be made to meet their unmet need. Present study attempts to assess the need for life skills among adolescents of secondary school. The data were collected from a sample of 264 adolescents from Classes IX and X of public and private schools of Etawah city with the help of self-administered questionnaire. Results of study revealed that 38.25 percent had low knowledge level of life skills and only 18.18 per cent showed high knowledge level of life skills and remaining 43.57 per cent were in the category of moderate knowledge of life skills. Students’ socio-economic status was significantly associated with their knowledge level of life skills. There is strong need to relate the education with the sensible aspect of life where student can be skillfully made responsible for his/her behaviour or actions and life skills education should become an integral part of education so an individual can operate effectively in society in an active and constructive way.